Isolasi dan Uji Aktivitas Antagonisme Jamur Endofit Tanaman Pisang (Musa paradisiaca L.) terhadap Fusarium oxysporum - Oktira Roka Aji; Aninda Kumala Sari; Diah Asta Putri (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Fungi that grow in plant tissue without harming the host are called endophytic fungi. This fungus has the potential as a biological agent (biocontrol) in controlling plant diseases. One of the fungi that can cause disease in banana plants is Fusarium oxysporum, which can cause Fusarium wilt disease. Endophytic fungi have antagonistic properties in the form of nutritional competition and antibiosis. These antagonistic properties can be used as biological agents. The purpose of this study was to isolate and test the antagonistic activity of the endophytic fungus of banana plant (Musa paradisiaca L.) against the pathogenic fungus Fusarium oxysporum. This research is an experimental study, which begins with the isolation of endophytic fungi and then continues with the antagonism activity test. The results of the isolation obtained 4 isolates of endophytic fungi, namely: 1) isolate D1 (Phytium sp.); 2) isolate B1 (Aspergillus sp.); 3) isolate A1 (Trichoderma sp.); and 4) isolate A2 (Penicillium sp.). Based on the antagonism activity test, isolate A1 showed the best results in inhibiting the fungus Fusarium oxysporum through the mechanism of space and nutrient competition, while isolates that showed antibiotic activity were isolate A2. The results of the inhibition test using the dual culture method showed that, 2 isolates (B1 and A2) could inhibit the growth of the fungus Fusarium oxysporum. The highest percentage of inhibition was owned by isolate A2. Based on its ability to inhibit Fusarium oxyaporum, endophytic fungal isolates have the potential to be further developed as Fusarium oxysporum control agents.